2018
DOI: 10.1007/s00784-018-2531-x
|View full text |Cite
|
Sign up to set email alerts
|

Screw-retained monolithic zirconia vs. cemented porcelain-fused-to-metal implant crowns: a prospective randomized clinical trial in split-mouth design

Abstract: Prosthetic retention methods are related with the occurrence of complications, such as peri-implantitis. However, scientific valuable data that proof superiority of a specific retention technique are rare. In single-gap implants, screw retention and cementation seemed to achieved comparable results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 25 publications
4
27
0
5
Order By: Relevance
“…These findings are in agreement with the data reported in previous clinical studies investigating monolithic zirconia implant‐supported crowns (Weigl et al., 2019; Worni et al., 2017). In these studies, no ceramic fractures were detected and a 100% reconstruction survival was reported.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are in agreement with the data reported in previous clinical studies investigating monolithic zirconia implant‐supported crowns (Weigl et al., 2019; Worni et al., 2017). In these studies, no ceramic fractures were detected and a 100% reconstruction survival was reported.…”
Section: Discussionsupporting
confidence: 93%
“…To date, only two clinical studies evaluating the use of monolithic zirconia for single implant crowns have been. A clinical study with a 1‐year follow‐up found 22 screw‐retained monolithic zirconia crowns to be free of ceramic chippings, whereas two chippings were detected in 22 cemented PFM crowns (Weigl et al., 2019). Another clinical study reported no technical complications of 18 monolithic zirconia implant crowns after an observation period between 12 and 36 months (Worni, Katsoulis, Kolgeci, Worni, & Mericske‐Stern, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Another clinical study compared the clinical performances of screw-retained monolithic zirconia and cemented metal-ceramic crowns, reporting that the DMBL was not correlated with the restoration method and that the 2 groups showed comparable clinical and radiological results after 12 months of follow-up. 25 The results of these clinical studies are consistent with those of previous in vitro studies. [16][17][18] In contrast, the results of a previous study showed that not only the implant system but also the prosthesis material had an effect on peri-implant bone.…”
supporting
confidence: 88%
“…Compared with the use of other ceramic materials, the use of monolithic zirconia also substantially reduces the invasiveness required for restoration preparation and thus contributes to a prosthetic restoration that preserves as much of the tooth structure as possible Today, monolithic zirconia is used for several indications. In addition to single crowns, the material is under evaluation for the fabrication of tooth and/or implant‐supported fixed partial dentures (FPDs), implant‐supported single crowns, and implant‐supported full‐arch prostheses . Future areas of clinical application are also being investigated, for example, prefabricated crowns for the treatment of deciduous teeth or posterior resin‐bonded FPDs …”
Section: Introductionmentioning
confidence: 99%